KOLOKASI FRASA VERBAL (FI‘IL) DAN PREPOSISI (ḤARF JAR) DALAM SURAT AN-NISA’ PADA TAFSIR AL-MISBAH KARYA M. QURAISH SHIHAB - Waki Ats Tsaqofi; Melfin Iza Farhatun Nazillah; Abdullah Abdullah; Ulil Abshar; Abdullah Maulani (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2022)
This study focuses on Arabic collocations in general. Arabic has a unique linguistic phenomenon that needs to be understood by itself. The questions that will be studied focus on verbal phrases that collocate with prepositions contained in Surat An-Nisa. The word collocation comes from English, which has the word collocate which means "to place." Whereas in Arabic, the word collocation has the equivalent meaning of المصاحبة الغاوية  (al-Muṣāḥabah al-Ghāwiyyah), among these collocations is الأفعال المتعدية بحروف الجر  (al-Af‘āl al-Muta'adiyyah bi Ḥurūf al-Jar) which is understood as a verb, which collocates with prepositions. This research method is described qualitatively by using the corpus of Tafsir Al-Misbah Volume 2 by M. Quraish Shihab. Qualitatively, the writer lists and finds the equivalent of the verb phrases that are placed with prepositions and explores a broader understanding. Descriptively, the researcher describes the data found by M. Quraish Shihab in Surah An-Nisa' on Tafsir Al-Misbah. Overall, the researcher found 20 everyday phrases with prepositions consisting of 19 Fi'il tsulatsi mujarrad and 1 Fi'il rubai'i. Based on the type of verb there are 11 Fi'il madzi, 5 Fi'il mudhori' and 4 Fi'il amr. Based on the category of collocation phenomena, there are 9 Tawarud basith phenomena and 11 Tawarud warid phenomena. Based on the semantic relationship of the meaning of the collocation phenomenon, there are three synonymous relationships, two oppositional relationships, and 15 complementary relationships.